The US National strategy for maritime security 2005 and its geopolitical implications on Malaysia - Ruhanie Ahmad, (Penerbit UKM, 2011)
This article is written on the assumption that Malaysia---a major littoral state to the Straits of Malacca and the South China Sea---may experience a delicate diplomatic situation resulting from the preemptive character of the US National Strategy for Maritime Security 2005---NSMS 2005---which could motivate rivalry, provoke conflict, and induce war in Southeast Asia. The assumption is such because the US is now perceived to be using NSMS 2005 as its latest geopolitical tool to contain China, to safeguard its energy security geopolitics, and in anticipation of maritime-based resource war in the region. The crux of this article, therefore, is based on the question how will Malaysia maintain its balanced relations toward the US and China in the context of this geopolitical framework. As such, this article attempts to analyze the preemptive character of NSMS 2005, to ascertain the China Factor contained in it, and to examine the impacts and implications of this maritime strategy on Malaysia’s future relations with the US and China. This analysis hopes to enlighten the Malaysian government on the geopolitical consequences of NSMS 2005 and to facilitate the Malaysian government with the appropriate insights on how to mitigate these consequences through foreign policy initiatives at the national, bilateral, and multilateral levels.